Developing sorghum crop as a source for biofuels. (Research'eu results magazine)
Sweet sorghum has many advantages over other crops when it comes to producing sugar for biofuel. An EU initiative has developed new hybrids, crop models and sustainability analyses to assist exploitation in numerous settings.